Depth-dependent magnetic crossover in a room-temperature skyrmion-hosting multilayer - Hicken, TJ; Wilson, MN; Salman, Z; Zhang, SL; Holt, SJR; Prokscha, T; Suter, A; Pratt, FL; van der Laan, G; Hesjedal, T; Lancaster, T (American Physical Society, 2024)
Skyrmion-hosting multilayer stacks are promising avenues for applications, although little is known about the depth dependence of the magnetism. We address this by reporting the results of circular dichroic resonant elastic x-ray scattering (CD-REXS), micromagnetic simulations, and low-energy muon-spin rotation (LE-μ+SR) measurements on a stack comprising [Ta/CoFeB/MgO]16/Ta on a Si substrate. Energy-dependent CD-REXS shows a continuous, monotonic evolution of the domain-wall helicity angle with incident energy, consistent with a three-dimensional hybrid domain-wall-like structure that changes from Néel-like near the surface to Bloch-like deeper within the sample. LE-μ+SR reveals that the magnetic field distribution in the trilayers near the surface of the stack is distinct from that in trilayers deeper within the sample. Our micromagnetic simulations support a quantitative analysis of the μ+SR results. By increasing the applied magnetic field, we find a reduction in the volume occupied by domain walls at all depths, consistent with a crossover into a region dominated by skyrmions above approximately 180 mT.